Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0266006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dynamic changes of peri-procedure anxiety and short-term prognosis in patients undergoing elective percutaneous coronary intervention for coronary heart disease: A single-center, prospective study

Abstract: Background Patients with coronary heart disease (CHD) often experience anxiety, but the current studies on anxiety mostly focused on a certain point in time. Therefore, this study aimed to investigate the dynamic changes of peri-procedure anxiety, status of post-procedure quality of life, and cardiovascular readmission rates in patients with CHD who undergoing elective percutaneous coronary intervention (PCI), and to analyze the influence of peri-procedure anxiety on quality of life and readmission rate after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…[96] Analysis of data from 2 prospective cohort studies, CKB and DFTJ, indicated that depression was associated with an increased risk of all-cause and CVD mortality (Table 12), particularly in men. [97] A longitudinal study to investigate anxiety and depression in CAD patients indicated that baseline/ 1-year depression, but not anxiety, were correlated with increased cumulative major adverse cardiovascular events (MACE) occurrence. [90] A single-center prospective study showed that peri-procedure anxiety was associated with the prognosis in CAD patients who underwent elective percutaneous coronary intervention (PCI).…”
Section: Psychological Factors Epidemiologymentioning
confidence: 99%
“…[96] Analysis of data from 2 prospective cohort studies, CKB and DFTJ, indicated that depression was associated with an increased risk of all-cause and CVD mortality (Table 12), particularly in men. [97] A longitudinal study to investigate anxiety and depression in CAD patients indicated that baseline/ 1-year depression, but not anxiety, were correlated with increased cumulative major adverse cardiovascular events (MACE) occurrence. [90] A single-center prospective study showed that peri-procedure anxiety was associated with the prognosis in CAD patients who underwent elective percutaneous coronary intervention (PCI).…”
Section: Psychological Factors Epidemiologymentioning
confidence: 99%
“…Diabetes mellitus, characterized by chronic hyperglycemia, augments atherosclerosis development and accelerates plaque vulnerability through mechanisms involving oxidative stress, inflammation, and endothelial dysfunction [13,14]. Hypertension, another key risk factor, exerts mechanical stress on arterial walls, promoting endothelial dysfunction and atherosclerosis initiation [15]. Furthermore, psychological factors such as chronic stress, depression, and social isolation have been linked to increased MI risk through mechanisms involving autonomic dysregulation, inflammatory responses, and unhealthy behaviors [16].…”
Section: Lifestyle Factors and Comorbiditiesmentioning
confidence: 99%
“…They can detect cTn levels within a few hours of symptom onset, compared to older assays that required several days to provide reliable results. The European Society of Cardiology (ESC) and the American College of Cardiology (ACC) guidelines recommend high-sensitivity cTn testing for diagnosing MI, underscoring its importance in clinical practice [15]. Another promising biomarker is the heart-type fatty acid-binding protein (H-FABP), which is released into the bloodstream rapidly after myocardial injury.…”
Section: High-sensitivity Biomarkersmentioning
confidence: 99%